Comparative Study on the Performance of Novel Electromagnetic Induction Heating and Electric Heating Turnout Snow Melting System - She, Yue; Wang, Qingfeng; Zhang, Jianqiong; Li, Xiangqiang (Archives of Electrical Engineering (Online), 2025)
This study addresses the issues of high energy consumption and low efficiency in conventional electric heating snow-melting systems for railway turnouts. A novel system is proposed that integrates electromagnetic induction heating with traditional electric heating to optimise energy transfer pathways and enhance energy utilisation efficiency. The system enables dynamic adjustment of heating power, thereby supporting adaptive operation under varying environmental conditions. Through theoretical analysis, temperature field simulations, and experimental validation, the energy regulation mechanism and performance characteristics are examined. Results show that, under full snow-cover conditions, the proposed induction heating system reduces snow-melting time by 76.9% compared with traditional electric heating, while achieving a 29% efficiency gain under snow-free conditions. Steady-state temperature rise tests demonstrate close agreement between simulations and measurements: directional heat transfer efficiency improves significantly, with the average rail temperature decreasing by 8.5% and the air temperature in the working area increasing by 15%. Additionally, the system increases the ice- and snow-melting rates by 0.4 and 0.8 times, respectively, while reducing energy consumption by 30–40%. An optimised composite thermal structure further enhances heat utilisation. This study provides both theoretical and practical insights for advancing turnout snow-melting technology and its engineering applications.